Laporan Kasus: Manifestasi Oral Penderita Hipertensi berupa Ginggival Enlargement - Anindita L.; Aris Aji K.; Arcadia Sulistijo J. (Fakultas Kedokteran Gigi Universitas Jember, 2020)
Hypertension presents an increase in blood pressure following the oral manifestations, such as gingival enlargement. A 42-year-old woman came to the General Sudirman University Dental and Oral Hospital complaining of enlarged front gums seven years ago. The patient had a history of hypertension and regularly consumed drugs, amlodipine 5 mg. Extraoral examination revealed no lymphadenopathy and no swelling of the head and neck area. Intraoral examination revealed a gingival enlargement involving the papilla to the gingival margin present on the entire upper and lower labial gingival surface. The patient's diagnosis was gingival enlargement caused by gingival enlargement due to the use of amlodipine. Gingival enlargement has been noted with long-term or high-dose amlodipine use. The mechanism of amlodipine in causing gingival enlargement is through the role of fibroblasts with abnormal susceptibility to the drug, resulting in increased levels of protein synthesis, especially collagen. The role of pro-inflammatory cytokines occurs through an increase in interleukin-1β (IL-1β) and IL-6 in the inflamed gingival tissue due to the gingival fibrogenic response to drugs. Therapies were DHE and scaling and root planning as phase I in periodontal treatment. Plaque elimination is vital to reduce gingival inflammation that may occur. Substitution of the drug amlodipine may be needed if there is no improvement. Based on case reports, hypertension patients who took amlodipine could have gingival enlargement. The therapy given was plaque elimination in the form of DHE and Scaling and regular check-ups with the dentist.